Establishing a model for intensity control in elite rowers using lactate threshold power - Huang, X.; Wu, H.; Wu, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: With the help of scientific research methods and physiological indices, coaches should be able to control an athletes` training intensity with the purpose of developing specific aerobic endurance or anaerobic glycolytic capacity. This paper involves an evaluation of measures of training intensity using ergometer tests. The program involved 8 elite Guangdong light weight female rowers who participated in the 2005 qualification regatta of the 10th National Games and 2005 World Cups. The Guangdong rowing team failed to reach the targeted performance in the qualification regatta. This failure provided the stimulus for the development of a training intensity control model using lactate-heart rate indices through "step load testing".